The Relationship between History of Breastfeeding and Obesity on Elementary School Children - Pakpahan, David Jhon Ricardo; Tanjung, Ika Citra Dewi; Hutagalung, Haflin Soraya (SCRIPTA SCORE Scientific Medical Journal, 2020)
ABSTRACT Obesity is a public health concern that its prevalence and intensity on children have been increasing with alarming status. Breastfeeding has been considered as one of protective factors that can prevent childhood obesity. The aim of this study is to discover the relationship between history of breastfeeding and obesity on elementary school children. This is an analytical study with cross sectional design. All children in first and second grade of Namira Islamic Elementary School and their mothers were included as population. Ninety samples were recruited randomly. Data on breastfeeding history were collected by using questionnaire guided interview from the mothers. The BMI-for-age curve CDC 2000 was used to determine obesity status of the children (â‰¥ 95th percentile). Data were analyzed using chi-square test. This study found percentage of children with and without history of breastfeeding consecutively is 92.2% and 7.8%. Prevalence of children with obesity is 12.2% and without obesity is 87.8%. Eight of 83 children with history of breastfeeding (72.7%) were obese, and 3 of 7 children without history of breastfeeding (27.3%) were obese (PR=0.2; 95% CI=0.27-0.752;p<0.05). Based on the study, there is a relationship between history of breastfeeding and obesity in elementary school children. Keywords: Breastfeeding, Elementary School Children, Obesity ABSTRAK Obesitas merupakan masalah kesehatan yang prevalensi dan intensitas kejadiannya pada anak terus meningkat serta telah mencapai status yang mengkhawatirkan. Pemberian ASI telah dipertimbangkan sebagai salah satu faktor yang dapat mencegah terjadinya obesitas pada anak. Tujuan dari penelitian ini adalah untuk mengetahui adanya hubungan antara riwayat pemberian ASI dengan kejadian obesitas pada anak sekolah dasar. Penelitian ini dilakukan melalui pendekatan analitik dengan desain cross sectional. Populasi penelitian ini adalah anak Sekolah Dasar Swasta Islam Namira yang berada di kelas satu dan dua dan Ibu nya. Jumlah sampel dalam peneltian ini adalah 90 orang yang dipilih secara acak. Data mengenai riwayat pemberian ASI didapatkan melalui wawancara dengan kuesioner dari Ibu. Kriteria obesitas pada anak ditentukan dengan menggunakan kurva indeks massa tubuh menurut usia dari CDC 2000 (persentil â‰¥95). Data yang didapat dianalisis dengan uji kai kuadrat. Pada penelitian ini ditemukan 92.2% anak mendapat ASI dan 7.8% anak tidak mendapat ASI saat bayi. Anak yang mengalami obesitas adalah 12.2% sedangkan anak yang tidak mengalami obesitas adalah 87.8%. Anak yang mendapat ASI dan mengalami obesitas adalah 72.7% sedangkan anak yang tidak diberi ASI dan mengalami obesitas adalah 27.3%. Berdasarkan hasil uji hipotesis didapatkan (RP=0.2; 95% CI=0.27-0.752: p<0.05). Berdasarkan hasil penelitian didapatkan bahwa terdapat hubungan antara riwayat pemberian ASI dengan kejadian obesitas pada anak sekolah dasar. Kata Kunci: Anak Sekolah Dasar, ASI, Obesitas